MODELLING OF AUTOMATIC CORRECTION OF MISTAKES IN TECHNOLOGY OF INFORMATION SYSTEMS - George N. Isaev (Открытое образование (Москва), 2016)
The model of automatic correction of mistakes is developed at processing documents of a tabulared kind within the framework of information systems of high school, the scientific organizations, etc. The corresponding program of the computer Is developed. The program exclude necessity of manual operations at updating mistakes in technology of processing of tabulared documents. Results of computer experiments have confirmed adequacy of model. Measurement is executed and technical and economic efficiency of model is shown.